The influence of learning environment and learning motivation on student achievement in Social Studies: A case study in Adiwiyata School - Azharotunnafi, Azharotunnafi; Nisak, Heppy Dwi Khoirun; Trisnawati, Diana (Universitas Negeri Yogyakarta, 2025)
This study aims to determine the influence of the learning environment and learning motivation on student achievement at SMP Negeri 1 Tumpang. The population of eighth-grade students is 294, and a sample of 169 students was obtained using cluster random sampling. The data collection techniques used are questionnaires and documentation. The distributed data was processed using a Likert scale. The data analysis techniques used are multiple linear regression analysis, classical assumption tests, t-tests, F-tests, and the coefficient of determination. The analysis results show that the environment has a positive partial effect on learning achievement, t calculated > t table (2.242 > 1.974), learning motivation has a positive partial effect on learning achievement, t calculated > t table (4.258 > 1.974), and both the learning environment and learning motivation simultaneously have a positive effect on learning achievement, F calculated > F table (22.690 > 3.05). Research findings indicate that the learning environment has a greater influence than motivation. This is supported by the school environment, which is an Adiwiyata-certified school. The environment created through the integration of learning based on environmental themes, the development of green areas, and the management of natural resources contributes significantly more than motivation. The advantages of the Adiwiyata program as a whole enable the school to enhance the quality of learning. It means that with a good environment, students feel comfortable to learn